Evaluation of three fish-derived probiotic bacteria replacing antibiotics on growth, immunity, gut morphology and disease resistance in juvenile olive flounder Paralichthys olivaceus fed reduced fish meal diets - Choi, Wonsuk; Moniruzzaman, Mohammad; Lee, Seunghan; Bae, Jinho; Bai, Sungchul C.; Min, Taesun; Lee, Seunghyung (Frontiers in Nutrition, 2025)
A basal diet without feed additives was used as a control (CON) and three diets were formulated by supplementing with Bacillus subtilis WB60 at 1 × 108 CFU/g (Pro-A), B. subtilis SJ10 at 1 × 108 CFU/g (Pro-B), Enterococcus faecium SH30 at 1 × 107 CFU/g (Pro-C), and two other diets supplementing with antibiotics such as amoxicillin (AMO) at 4 g/kg and oxytetracycline (OTC) at 4 g/kg of the basal diet. A total of 450 fish averaging 12.1 ± 0.09 g (mean ± SD) were fed one of the six experimental diet groups in triplicates for 8 weeks. In disease resistance test, 45 fish from each group were intraperitoneally injected with the pathogenic bacteria, Edwardsiella tarda, and mortality was recorded for 15 days. At the end of 8-week feeding trial, weight gain, specific growth rate and feed efficiency of fish fed the Pro-A diet were significantly greater than those of fish fed the CON, OTC and AMO diets (p < 0.05). Furthermore, feeding efficiency and protein efficiency ratio of fish fed the Pro-A diet were significantly greater than those of fish fed the CON, OTC and AMO diets. Serum aspartate aminotransferase levels were significantly greater in fish fed the Pro-B diet than in those fed the Pro-A diet. The lysozyme activity of fish fed the Pro-A, Pro-B and Pro-C diets was significantly greater than that of the CON, OTC and AMO diets. The myeloperoxidase activity of fish fed the Pro-A diet was significantly greater than that of the fish fed the CON and AMO diets. The flounder growth hormone levels of fish fed the Pro-A, Pro-B, Pro-C and AMO diets were significantly greater than that of the fish fed the CON diet. The interleukin 1β gene expression levels in fish fed the Pro-B and Pro-C diets were significantly greater than those in fish fed the CON, OTC and AMO diets. The interleukin 10 gene expression levels in fish fed the Pro-A, Pro-B, Pro-C and OTC diets were significantly greater than those of fish fed the CON and AMO diets. Intestinal histology revealed that the average villi length of fish fed the Pro-A, Pro-B, and Pro-C diets were significantly greater than that of fish fed the CON, OTC and AMO diets. The cumulative survival rates of fish fed the Pro-A, Pro-B and Pro-C diets were significantly greater than those of fish fed the CON diet after the 15th day of the challenge test. Overall, the results demonstrated that the supplementation of fish-derived bacteria, B. subtilis (1 × 108 CFU/g diet) or E. faecium (1 × 107 CFU/g diet) in the diet could be the ideal probiotics to replace antibiotics in olive flounder fed FM reduced diet.